Understanding Construction Contracts Canadian and International Conventions - Surahyo, Akhtar (Springer International Publishing, 2018)
This book provides an overall understanding of construction contracts, explaining a range of topics with in-depth examples, allowing engineers, site managers, architects, contractors, and other construction professionals in search of information on construction contracts to find it in one place. The volume further serves as a learning tool and a reference guide for students and instructors. Adopting a primarily Canadian perspective, the book provides references from two Standard Contract Documents CCDC (Canadian Construction Document Committee) and FIDIC (International Federation of Consulting Engineers) and briefly describes other major contract documents used within USA and UK construction industries. Offers a comprehensive overview of construction contracting topics including contract delivery methods, construction documents, insurance and bonds, construction payments, claims and dispute resolution procedures recommended by CCDC and FIDIC conditions of contract, and how to administer and close a contract; Addresses in detail the various types of delays: excusable and non-excusable delays, compensable and non-compensable delays, including acceleration; Various types of changes are defined for deeper understanding of the reader, including directed changes, constructive changes, concurrent delays, cardinal changes, differing site conditions and disruption; Provides a better understanding about the competitive bidding process, information on "Contract A" and "Contract B", qualified bids, responsive and non-responsive bids, and how to handle identical low and tied bids; Delivers insights on analyzing and managing construction risks based on the author's 30+ years' experience as a professional engineer; Adopts an easy and concise, step-by-step description of construction contracts, including work examples, tables and legal citations.